RANCANG BANGUN SISTEM INFORMASI RENCANA ANGGARAN BIAYA (RAB) PERUSAHAAN BERBASIS WEB PADA PT. BUMITANGERANG MESINDOTAMA - Anita B. Wandanaya; Andrian Wicaksono (UNIVERSITAS RAHARJA, 2018)
The cost budget plan is one of the controls in the management of a project that will be planned in the company, if in the planning of a project there is no budget plan then a project will be ambiguous in making the report, it also needs to be applied to PT. Bumitangerang Mesindotama to facilitate companies in planning the costs. Therefore, it is necessary to have a system that can produce output in the form of detailed reports for planning company budget costs in meeting the procurement system of a project plan. In this study a web-based system is implemented for planning project cost budgets in companies, therefore it is necessary to design a web-based company budget plan system. This system uses web-based input in the process of filling out project activities, details of required materials and budget planning of the required costs so that it can produce final reports in the form of the neat recapitulation. With the creation of a cost budget plan system is expected to solve existing problemsand the company no longer needs to use a manual way to plan budget costs, so that the budget planning process can run more quickly and accurately. In this study, researchers used the System Development Life Cycle (SDLC) method which was supported by data collection through observation and literature study.